Comparison of Various Vagal Maneuvers for Supraventricular Tachycardia by Network Meta-Analysis - Huang, Edward Pei-Chuan; Chen, Chi-Hsin; Fan, Cheng-Yi; Sung, Chih-Wei; Lai, Pei Chun; Huang, Yen Ta (Frontiers in Medicine, 2022)
Background: Vagal maneuvers (VagMs) are recommended as the first-line treatment of supraventricular tachycardia (SVT). However, the optimal type of VagMs remains unproven. Aim: This study aims to compare the effectiveness and adverse events amongst VagMs on SVT via network meta-analyses (NMAs). Methods: We systematically searched randomised controlled trials (RCTs) that involved adults with SVT and compared VagMs without language restrictions. We determined the initial and final responses of conversion rate to sinus rhythm and adverse events. NMAs were synthesised using the frequentist random-effects model and presented as relative risk (RR) with 95% confident interval (CI). The order of probability was presented surface under the cumulative ranking curve analysis (SUCRA). Sensitivity analysis using both Bayesian and frequentist approach with fixed- or random-effects models. Certainty of evidence (CoE) was rated by using the Grading of Recommendations, Assessment, Development and Evaluations methodology. Results: Fourteen RCTs with 2180 patients were enrolled. Compared with carotid sinus massage (CSM), the modified Valsalva maneuver (MVM) was the most effective VagM after initial performance (SUCRA: 0.9992, RR: 5.47 [1.77–16.93]) and at the end of study (SUCRA: 1.0000, RR: 3.62 [2.04–6.39], CoE: high). The standard VM did not elicit better conversion rate to the sinus rhythm than CSM at the initial response (SUCRA: 0.4395, RR: 1.97 [0.63–6.15]) and at the end of the study (SUCRA: 0.4795, RR: 1.64 [0.94–2.87], CoE: moderate). The SUCRA value of CSM at the initial and final responses was the least one amongst three VagMs (0.0613 and 0.0205, respectively). Adverse events amongst three VagMs were similar (CoE: low). Sensitivity analyses yielded consistent results. Conclusions: We recommended MVM as the first choice of VagM for rhythm conversion before the pharmacological management of SVT.